The Utilization of Pasak Bumi Plants (Eurycoma longifolia Jack.) as Traditional Medicine and Its Bioactivity - Marina Silalahi (HM Publisher, 2020)
Pasak bumi (Eurycoma longifolia Jack.) is a species belonging to Simarobuaceae that has been long used as traditional medicine, which is known very well as an aphrodisiac. The studies have been conducted to reveal the benefits of E. longifolia through ethnobotany, phytochemical, and bio essay approaches, but the review articles on its utilization and bioactivity are limited. This article is based on scientific articles published online or offline, then synthesized so that to be information on the relationship between use and bioactivity. Ethnobotany of E. longifolia has been used as a medicine for fever, malaria, improved stamina, diabetes, cancer, aphrodisiac, and erectile dysfunction. The bioactivity of E. longifolia is antiosteoporotic, antimicrobial, aphrodisiac, anticancer, angiogenesis, and hepatoprotective. Eurycomanone is a secondary metabolite in E, longifolia has activity as an antimalaria, antipyretic, aphrodisiac, and cytotoxic. The quassinoids, coumarin, and glycosides of El have activity increase the production, quality, totality, synthesis, and release of spermatozoa. Eurycoma longifolia is very potential to be developed as an antiosteoporotic and a prosidiac drug, but until now most of it is harvested directly from the forest, so to preserve it, we need to study the cultivation method.